Diatoms (Bacillariophyceae) of Iguacu National Park, Foz do Iguacu, Brazil - Rodrigues Bartozek, Elaine Cristina; Bueno, Norma Catarina; Veiga Ludwig, Thelma Alvim; Tremarin, Priscila Izabel; Nardelli, Margaret Seghetto; Righetti da Rocha, Angelica Cristina (Soc Botanica Brasil, 2013)
This study represents a taxonomic survey of class Bacillariophyceae diatoms found in samples collected in the Iguacu River (Iguacu National Park, municipality of Foz do Iguacu, in the state of Parana, Brazil) between August 2007 and July 2008. Two sampling stations were utilized, the first located upstream of Iguacu Falls (Cais Bananeiras Station) and second downstream of the falls (Cais Macuco Safari Station). The study resulted in the identification of 86 taxa, including 74 at the specific level and seven taxonomic varieties. Two of these had never before been documented in the state of Parana: Gomphonema gibberum Hustedt and Pinnularia meridiana Metzeltin & Krammer. Nine are first-time records for Brazil: Cymbella charrua Metzeltin, Lange-Bertalot & Garcia-Rodriguez, Placoneis ovillus Metzeltin, Lange-Bertalot & Garcia-Rodriguez, Gomphonema affinopsis Metzeltin, Lange-Bertalot & Garcia-Rodriguez,, Gomphosphenia lingulatiformis (Lange-Bertalot & Reichardt) Lange-Bertalot, Luticola aequatorialis (Heiden) Lange-Bertalot & Ohtsuka, Sellaphora garciarodriguezii Metzeltin & Lange-Bertalot, Eolimna submuralis (Hustedt) Lange-Bertalot Kulikovskiy, Geissleria neosubtropica Metzeltin, Lange-Bertalot & Garcia-Rodriguez and Stauroneis cf. sylviabonillae Metzeltin, Lange-Bertalot & Garcia-Rodriguez.
Keywords: taxonomy; microalgae; lotic system; state of Parana